Answer:
see explanation
Explanation:
(4)
6 = hj + k ( subtract k from both sides )
6 - k = hj ( isolate j by dividing both sides by h )
= j
(5)
= 9 ( multiply both sides by w to clear the fraction )
9w = v ( divide both sides by 9 )
w =
(8)
A =
bh ( multiply both sides by 2 to clear the fraction )
2A = bh ( divide both sides by h )
= b
(10)
V =
πr²h ( multiply both sides by 3 to clear the fraction )
3V = πr²h ( isolate h by dividing both sides by πr² )
= h
(12)
V = πr²h ( isolate r² by dividing both sides by πh )
= r² ( take square root of both sides )
= r